2021
DOI: 10.1002/aoc.6205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characterization, density functional theory studies, and biological screening of some transition metal complexes of a novel hydrazide–hydrazone ligand of isonicotinic acid

Abstract: Highlights• A new hydrazide-hydrazone ligand of isonicotinic acid was synthesized. • Seven mononuclear Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Hg(II) complexes of the new ligand were prepared and characterized by different tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 82 publications
0
21
0
3
Order By: Relevance
“…3 T 1g (P) (ν 3 ) transitions, respectively. [53,58] The magnetic moment value of Ni(II) complex (3.45 B.M.) along with its electronic transition bands confirms the high-spin octahedral environment around Ni(II) ions.…”
Section: Electronic Spectra and Magnetic Moment Studiesmentioning
confidence: 68%
See 2 more Smart Citations
“…3 T 1g (P) (ν 3 ) transitions, respectively. [53,58] The magnetic moment value of Ni(II) complex (3.45 B.M.) along with its electronic transition bands confirms the high-spin octahedral environment around Ni(II) ions.…”
Section: Electronic Spectra and Magnetic Moment Studiesmentioning
confidence: 68%
“…[51,52] However, the spectrum of Cu(II) perchlorate complex (6) displays a splitted band at 1079, 1075, and 622 cm À1 , compatible with a monodentate chelation of perchlorate group. [53][54][55] The previously mentioned data along with the absence of vibrational modes of ÀOH group are ruling out tautomerism and confirm the neutral behavior of the ligand that acts as a bidentate one through amino nitrogen and carbonyl oxygen atoms.…”
Section: Infrared Spectral Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…In evaluating the antioxidant activity of MD, one has to also consider that pyridines are very good coordinating ligands and therefore it is highly likely that MD forms chelates with trace metals [5,6]. Previous studies showed that the presence of transition metals such as Cu(I) can produce hydroxyl radicals via the Fenton-like reaction (1.1) [7][8][9][10][11]:…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they are important compounds for drug design, as possible ligands for metal complexes, organo-catalysis and also for the syntheses of heterocyclic compounds [10]. In recent years, a lot of biologically important hydrazide-hydrazones derivatives have been synthesized from different carbonyl compounds [11] [12] [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%